Karagenan Rumput Laut Merah Bali (Gracilaria sp.) sebagai Antibakteri terhadap Delapan Bakteri Patogen - Sasadara, Maria Malida Vernandes; Cahyaningsih, Erna; Dewi, Ni Luh Kade Arman Anita; Yuda, Putu Era Sandhi Kusuma; Wardani, I Gusti Agung Ayu Kusuma; Juliadi, Debby; Putri, Ni Kadek Dila Pratiwi; Putri, Ni Kadek Nisa Leoni; Darmawan, I Wayan Agus; Yanti, Ni Kadek Pradnya (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2025)
The increase in infection cases every year, coupled with the rise in resistance cases, increases the urgency of exploring antimicrobial agents. Gracilaria sp. is a red seaweed that is widely known as one of the potential producers of active metabolites, sulfated polysaccharides. Carrageenan is one form of sulfated polysaccharide that has antimicrobial activity. This study was conducted to evaluate the antibacterial activity of carrageenan derived from Gracilaria sp. against several pathogenic bacteria, including Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis, Klebsiella pneumoniae, Pseudomonas aeruginosa, Enterococcus faecalis, Streptococcus pyogenes, and Salmonella typhi. Carrageenan was extracted from Gracilaria sp. samples obtained from the South Denpasar area (Bali) using KOH. An antibacterial activity assay of carrageenan was carried out using an agar well diffusion method with nutrient agar media. Tests were conducted at concentrations of 1 and 5 mg/mL (E. coli and S. epidermidis), 20, 30, 40 mg/mL (S. aureus, S. pyrogenes, E. faecalis, and S. typhi), 50, 75, and 100 mg/mL (P. aeruginosa and K. pneumoniae). Incubation was carried out for 24 hours at ± 37 °C. Data were analyzed statistically by one-way ANOVA and Kruskal-Wallis with a 95% confidence level. The results showed that carrageenan extracted from Gracilaria sp. exhibited significant antibacterial activity against several pathogenic bacteria, especially gram-negative bacteria. The antibacterial activity produced in this study was proportional to the increase in concentration, where the inhibitory activity produced increased as the concentration of carrageenan increased. It can be concluded that carrageenan has the potential to be an antibacterial.